The teacher education program of the Philippine College of Arts and Trades implications for teacher education in Thailand - Tichantuik, Vichit 1942- (s.n.], 1972)
This paper investigates the teacher education curriculum, as well as the practices and implementation of rules and regulations, as the base for developing implications in Thailand.